Free Flap Head and Neck Reconstruction with an Emphasis on Postoperative Care - van Gijn, Daniel Richard; D'Souza, Jacob; King, Wendy; Bater, Michael (Facial Plastic Surgery, 2018)
Microsurgical free tissue transfer represents the mainstay of care in both ablative locoregional management and the simultaneous reconstruction of a defect. Advances in microsurgical techniques have helped balance the restoration of both form and function—decreasing the significant morbidity once associated with large ablative, traumatic, or congenital defects—while providing immediate reconstruction enabling early aesthetic and functional rehabilitation. There are a multitude of perioperative measures and considerations that aim to maximize the success of free tissue transfer. These include nutritional support, tight glycemic control, acknowledgment of psychological and psychiatric factors, intraoperative surgical technique, and close postoperative monitoring of the patients' hemodynamic physiology. While the success rates of free tissue transfer in experienced hands are comparable to alternative options, the consequences of flap failure are catastrophic—with the potential for significant patient morbidity, prolonged hospital stay (and associated increased financial implications), and increasingly limited options for further reconstruction. Success is entirely dependent on a continuous arterial inflow and venous outflow until neovascularization occurs. Flap failure is multifactorial and represents a dynamic process from the potentially reversible failing flap to the necrotic irreversibly failed flap—necessitating debridement, prolonged wound care, and ultimately decisions concerned with future reconstruction. The overriding goal of free flap monitoring is therefore the detection of microvascular complications prior to permanent injury occurring—identifying and intervening within that critical period between the failing flap and the failed flap—maximizing the potential for salvage. With continued technique refinement, microvascular free flap reconstruction offers patients the chance for both reliable functional and aesthetic restoration in the face of significant ablative defects. The caveat to this optimism is the requirement for considered perioperative care and the optimization of those factors that may offer the difference between success and failure.
Keywords: microvascular; free tissue transfer; perioperative care; surgical optimization; head and neck